ANALISIS KEMAMPUAN LITERASI DIGITAL SISWA KELAS V SDN TANJUNG JATI 2 DALAM PENGGUNAAN MULTIMEDIA INTERAKTIF PADA MATERI "BUMIKU SAYANG, BUMIKU MALANG" - Ida Fitriyani; Dya Qurotul A’yun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Advances in digital technology in education require students to have adequate digital literacy skills to optimize the use of interactive multimedia in learning. However, not all elementary school students have optimal digital literacy skills, especially in rural areas such as Bangkalan Regency. This study aims to analyze the digital literacy skills of fifth-grade students at Tanjung Jati 2 Elementary School in Bangkalan in the use of interactive multimedia in the material “My Beloved Earth, My Poor Earth.” This study uses a descriptive method with a qualitative approach. Data collection techniques include semi-structured interviews with teachers, observation of students' digital literacy skills, student response questionnaires, and interactive quizzes. Data analysis uses the Miles and Huberman model with the stages of data collection, data reduction, data presentation, and conclusion drawing. The research subjects consisted of fifth-grade teachers and 17 students. The results showed that 11 of the 17 students (64.7%) had mastered digital literacy skills at the maximum level in terms of opening applications, navigating pages, selecting interactive elements, and participating in quizzes. Students showed high enthusiasm for learning using interactive multimedia. However, the effectiveness of interactive multimedia in improving material comprehension was still less than optimal due to inappropriate implementation strategies, where Chromebook access was provided too early, thereby disrupting students' concentration during material explanations.